PENGARUH MODEL PROBLEM BASED LEARNING DAN KEMAMPUAN BERPIKIR KREATIF TERHADAP HASIL BELAJAR SEJARAH DI SMA KORPRI BEKASI - Muhammad Irham Romadhon; Sarkadi Sarkadi; Abdul Syukur (Jurnal Pendidikan Sejarah Indonesia, 2021)
This research aims to find out the effects of Problem Based Learning (PBL) and creative thinking skills on the instructional outcomes of the history of students at SMA KORPRI Bekasi. This research is a quantitative study using an experimental design of 2x2. The population consists of all students of class X IIS at SMA KORPRI Bekasi. The sample in this research consists of two classes, namely class X IIS 1 and X IIS 2 with a total of 60 students. A multiple-choice test was administered to measure students’ learning outcomes on history. A questionnaire was also used to uncover and categorize students' creative thinking. The results of this study indicate that: (1) students who were given problem-based learning models had higher learning outcomes in history compared to those who were given the direct learning models during historical instruction, (2) there was an interaction effect of learning models and creative thinking, (3) students who were given PBL and have high creative thinking skills had higher learning outcomes compared to those who were given a direct learning model and had high creative thinking skills, and (4) interestingly, a student with lower critical thinking skills got lower learning outcomes with PBL comparing those who had lower critical thinking skills and were given direct learning model. Hence, the result of this study indicates that there was an influence of the PBL model and creative thinking on the students learning outcomes in historical instruction at SMA KORPRI Bekasi.